Hazard assessment of the Tsho Roipa Glacier Lake and ongoing remediation measures - Rana, Birbal; Shrestha, Arun B.; Reynolds, John M.; Aryal, Raju; Pokhrel, Adarsha P.; Budhathoki, Kamal P. (Journal of Nepal Geological Society, 2000)
The Tsho Rolpa Glacier Lake stores about 100x 106 m3 of water behind an unconsolidated moraine dam in the Roiwaling Valley of central Nepal. The 150 m high terminal moraine has been deteriorating rapidly since the last 4-5 years, as buried dead-ice is being exposed. Displacement waves formed by the calving of the Trakarding Glacier terminus into the Tsho Rolpa are increasing in magnitude. Seepage from springs on the distal flank of the end moraine some 50 m below the dam crest and shallow slumps were also observed, and all of these phenomena indicate deterioration of the moraine dam. The majority of past studies suggested lowering the lake level to prevent a glacier lake outburst flood. Engineering work to lower the lake level down to 3 m by constructing an open channel on the terminal moraine began in May 1999 and ended successfully in July 2000. Several studies, including the ground penetrating radar survey, were conducted in association with the construction work. They provided the detailed information on subsurface conditions of the lake area. The construction of the open channel reduced the volume of water available to form a potential glacier lake outburst flood by about 20%. This work demonstrated for the first time in Nepal that such remediation of a glacier lake outburst is quite effective.